A new era in the treatment of multiple sclerosis. Issue 3 (3rd August 2015) - Broadley, Simon A; Barnett, Michael H; Boggild, Mike; Brew, Bruce J; Butzkueven, Helmut; Heard, Robert; Hodgkinson, Suzanne; Kermode, Allan G; Lechner‐Scott, Jeannette; Macdonell, Richard AL; Marriott, Mark; Mason, Deborah F; et al.
Summary: Multiple sclerosis (MS) is an autoimmune disease of the central nervous system with a multifactorial aetiology and highly variable natural history. A growing understanding of the immunopathogenesis of the condition has led to an expanding array of therapies for this previously untreatable disease. While a cure for MS remains elusive, the potential to reduce inflammatory disease activity by preventing relapses and minimising disease progression is achievable. The importance of early treatment in minimising long‐term disability is increasingly recognised. Most of the newer, more effective therapies are associated with risks and practical problems that necessitate an active management strategy and continuous vigilance. While the initiation of these therapies is likely to remain the responsibility of neurologists, other specialist physicians and general practitioners will be involved in the identification and management of adverse effects.